Electrophysiological effects of polyethylene glycol modified gold nanoparticles on mouse hippocampal neurons. Issue 12 (December 2020) - Tuna, Bilge Guvenc; Yesilay, Gamze; Yavuz, Yavuz; Yilmaz, Bayram; Culha, Mustafa; Maharramov, Akif; Dogan, Soner
Abstract: Gold nanoparticles (AuNPs) can cross the blood brain barrier, thus can be used as nanocarriers in brain drug delivery. However, the effect of bare and polyethylene glycol-modified (PEGylated) AuNPs on normal neural function has not been extensively investigated. In this study, bioelectrical properties of neuronal functions of male BALB/c mice were explored ex vivo and in vivo by using 5 nm bare AuNPs and PEGylated AuNPs. Electrophysiological properties of neurons from hippocampal CA1 region sections were recorded by patch clamp method. Ex vivo, firing rate of action and membrane potentials in response to negative current stimuli significantly altered only after bare AuNP exposure compared to control (p < 0.05). After in vivo injections, anxiety levels of animals were similar. Amplitude of action potentials reduced only in bare AuNP group (p < 0.05). In conclusion, excitability of hippocampal neurons is increasing with bare AuNP exposure, and PEGylation might be more biocompatible for medical applications. Abstract : Gold nanoparticles, Polyethylene glycol, Action potential, Functional neurotoxicity, Electrophysiology.